A comparative study of the effectiveness of a combination of oral trimeprazine/methadone and oral ketamine/midazolam as sedation for children in dental procedures - Louw, Louis Rontgen (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.